EMorF - A tool for model transformations - Klassen, Lilija; Wagner, Robert (Electronic Communications of the EASST, 2012)
In this paper, we present EMorF - a model transformation tool for EMF. EMorF supports the specification and execution of in-place model transformations as well as model-to-model transformations. The graphical though formal specification is based on (triple-) graph grammars, which are executed by an interpreter system. In this paper, we focus on the provided tool support for the development and execution of model transformations.